Antimicrobial Activity of Compounds Isolated from Uvaria wrayi (King) L.L. Zhou, Y.C.F. Su & R.M.K. Saunders Leaves and Twigs - Phukhatmuen, Piyaporn; Promnart, Phunrawie; Cheenpracha, Sarot; Laphookhieo, Surat; Winyayong, Panom (Trends in Sciences, 2024)
Antimicrobial resistance (AMR) refers to the capacity of bacteria to resist the impact of antibiotics, emerging as a significant global health concern. To discover novel antibacterial agents, the isolation and elucidation of compounds from leaf and twig extracts of Uvaria wrayi (King) L.L. Zhou, Y.C.F. Su & R.M.K. Saunders were investigated for the first time. 9 known compounds were performed and categorized as polyoxygenated cyclohexenes (1-3), seco-cyclohexenes (4), acrylamide derivatives (5,6), and aristolactam alkaloids (7-9). All isolated compounds were evaluated for their antimicrobial activities against 5 Gram-positive bacteria, including Staphylococcus aureus (TISTR 746), Staphylococcus epidermidis (DMST 15505), Methicillin-resistant Staphylococcus aureus (MRSA) (NPRC 001R), Cutibacterium acnes (formerly Propionibacterium acnes) (DMST 14916), and Streptococcus mutans (DMST 18777/ATCC 25175T). 2 Gram-negative bacteria, Shigella flexneri (DMST 4423) and Salmonella enterica ser. typhimurium (TISTR 2519) were evaluated. Most of the isolated compounds displayed moderate antimicrobial activity with a MIC value of 64 µg/mL, except compounds 1,9 showed antibacterial against MRSA with a MIC value of 128 µg/mL. Compounds 2-9 exhibited antimicrobial activity against C. acnes (DMST 14916) with a MIC value of 32 µg/mL. Compounds 1-3, 6, and 7 also responded to inhibit C. acnes with the same MBC value of 128 µg/mL. This exploration holds promise for advancing our understanding of potential antibacterial compounds within U. wrayi and addressing the challenges posed by antimicrobial resistance. HIGHLIGHTS The first phytochemical investigation of U. wrayi resulted in the isolation and identification of nine antibactiral compounds. Compounds 2-9 exhibited antimicrobial activity against Cutibacterium acnes (DMST 14916) with a MIC value of 32 µg/mL. Most of the isolated compounds displayed moderate antimicrobial activity with a MIC value of 64 µg/mL. GRAPHICAL ABSTRACT